2017
DOI: 10.1016/j.jtumed.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics of human diseases and scope in future therapeutics

Abstract: Epigenetics is the study of nucleotide modifications that are heritable and act as regulatory mechanisms without changing the nucleotide sequence of the genome. Exogenous cues such as environment, lifestyle, nutrition, stress, and psychological factors affect epigenetic mechanisms. This mechanism is in concordance with the genetic information that plays an important role during prenatal and postnatal life of an individual. Recent epigenetic studies have revealed the potential of epigenetics in elucidating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…The etiology as well as the outcome of most psychiatric and somatic/neurologic disorders is multidimensional and predicated on complex interactions between genes and environmental factors. Aberrations of epigenetic mechanisms are critical factors in the initiation and progression of many disorders and diseases (Shamsi et al 2017). It is well confirmed that many psychiatric disorders (schizophrenia, bipolar disorder, recurrent depression) and neurologic (Parkinson's disease, Alzheimer's disease and other dementias, multiple sclerosis) are associated with aging, epigenetic alterations (see table 4), a loss of neurons and glial cells, and neuro-degeneration.…”
Section: Epigenetics Of Resilience Comorbidity and Treatment Outcomementioning
confidence: 96%
See 1 more Smart Citation
“…The etiology as well as the outcome of most psychiatric and somatic/neurologic disorders is multidimensional and predicated on complex interactions between genes and environmental factors. Aberrations of epigenetic mechanisms are critical factors in the initiation and progression of many disorders and diseases (Shamsi et al 2017). It is well confirmed that many psychiatric disorders (schizophrenia, bipolar disorder, recurrent depression) and neurologic (Parkinson's disease, Alzheimer's disease and other dementias, multiple sclerosis) are associated with aging, epigenetic alterations (see table 4), a loss of neurons and glial cells, and neuro-degeneration.…”
Section: Epigenetics Of Resilience Comorbidity and Treatment Outcomementioning
confidence: 96%
“…Epigenetic alterations are involved in a diverse set of processes and implicated in a variety of mental disorders and somatic diseases. The reversibility of epigenetic defects makes epigenetic disorders and diseases amenable to therapeutics (Shamsi et al 2017) while the identification of epigenetic dysfunctions gives an opportunity to consider new treatment approaches (Tripathy 2011). The concept of translational medicine implies the application of latest scientific research in diagnostics, prevention and treatment of diseases, all in the spirit of evidence based medicine for the best patients' outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic modifications are inherited characteristics that are not caused by changes in the DNA sequence, as they result from changes in gene expression due to changes in DNA accessibility or chromatin structure ( 15 ). They are reversible modifications in gene function, involving overexpression or silencing of genes by mechanisms that do no result in DNA alterations, therefore being responsible for changes in the phenotype without genotypic alterations ( 16 , 17 ).…”
Section: Epigeneticsmentioning
confidence: 99%
“…The epigenetics represents alterations in genetic functions without changing DNA sequence and constitutes an interface of genetic/ environmental factors interplay, e.g. DNA methylation, histone modifications, non-coding RNAs regulation and higher order chromatin remodeling [28]. MiRNAs are 18-22 nucleotide long, non-coding RNAs that are involved in post-transcriptional suppression of gene expression [29].…”
Section: Genetics and Epigenetics Of Admentioning
confidence: 99%